2018
DOI: 10.1002/aoc.4478
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium/Phosphine catalysed selective hydroformylation of biorenewable olefins

Abstract: This work reports rhodium catalyzed selective hydroformylation of natural olefins like eugenol, estragole, anethole, prenol and isoprenol using biphenyl based Buchwald phosphine ligands (S‐Phos (L1), t‐Bu XPhos (L2), Ru‐Phos (L3), Johnphos (L4) and DavePhos (L5). Ru‐Phos (L3) ligand exhibited high impact on the hydroformylation of eugenol providing high selectivity (90%) of linear aldehyde as major product. In addition, internal natural olefins like anethole and prenol provided moderate to high selectivity (65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…1,2 Co-based and Rh-based catalysts are commonly used in industry. 3,4 Among them, Co-based catalysts exhibit low activity and need harsh reaction conditions. Comparatively, Rh-based catalysts with high activity and relatively mild reaction conditions have gradually become hotspots for research.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Co-based and Rh-based catalysts are commonly used in industry. 3,4 Among them, Co-based catalysts exhibit low activity and need harsh reaction conditions. Comparatively, Rh-based catalysts with high activity and relatively mild reaction conditions have gradually become hotspots for research.…”
Section: Introductionmentioning
confidence: 99%
“…Today, this transformation represents one of the most large-scale reactions in industry. More than ten million tons of "oxo chemicals" are manufactured by the hydroformylation reaction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As well known, the hydroxymethylation is an important reaction for introduction of a hydroxymethyl group into a molecular. [15][16][17][18][19][20][21][22] It has been reported that BAs could be synthesized via hydroxymethylation of aryl halides and triflates [23] ; however, the catalyst was rather complicated and high loadings (the combination of 5 mol % Pd (dba) 2 , 12 mol% Ru-phos, and 1.5 equiv. Na 2 CO 3 ), and the reactants were expensive resulting in a high-cost route.…”
Section: Introductionmentioning
confidence: 99%